Strategi Marketing Affiliate Make Up di Desa Mojopilang - Muhammad Faqih; Sari Indah Lestari; Khalilia Nur Iswati; Faizal Bakhri; Puspita Dwi Ningrum; Virgiawan Yusuf Candra; Muhammad Mahrus Ali Matriks Sugiyanto; Rahardian Adiptya; Widya Nila Ari Wibowo; Salsa Billa Nur Laila; Nikmah Rohmatul Hidayah; Siska Dyah Alfina; Nusantara Wau; Noventa Sabatini; Rizki Prima Meida; Rachmad Ifandy; An-Nisa Nur Hidayah; Alif Putra Pratama; Natasya Nur Cahya Farida; Annisa Aprilliawati; Muhammad Khoirul Rozikin; Sofiyana Yasmin (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
This research aims to increase UMKM opportunities in Mojopilang Village. In this increasingly modern and sophisticated era, technology, especially social media, is growing rapidly and making things easier for its users. This is very profitable for looking for business opportunities, one of which is affiliate. This research uses an outreach method which includes training on how to create an affiliate account, mentoring to ensure that the training carried out can be applied, correct make-up procedures to maximize affiliate content, as well as evaluation in the form of questions and answers. This activity was carried out on December 13 2024, involving village communities, especially women and Mayjen Sungkono University students. Initial observation results show that several people in Mojopilang Village have the mindset that if they want to open a business, they must spend capital and have very little knowledge about affiliates. Through this outreach about affiliate make up, it is hoped that the village community, especially women, will understand and be interested in doing affiliate work, especially in the field of make up. The results of this evaluation can be seen from the enthusiasm of the socialization participants who were excited about the material presented and some of them even wanted to try becoming affiliates.